On the soft Ds-dense and Dc-dense in soft ideal topological spaces. Issue 5 (4th July 2022) - Al-Swidi, Luay A.; Qahtan, Ghassan Adnan; Hadi, Mustafa Hasan; Omran, Ahmed A.
Abstract: The research is based on two basic principles: soft local function and soft Ψ-operation to construct the new concepts of density called Ds -dense and Dc -dense. Through these concepts, we defined a new type of separation axiom, which we called soft ST 1 -space.